2014
DOI: 10.7717/peerj.408
|View full text |Cite
|
Sign up to set email alerts
|

Prey aggregation is an effective olfactory predator avoidance strategy

Abstract: Predator–prey interactions have a major effect on species abundance and diversity, and aggregation is a well-known anti-predator behaviour. For immobile prey, the effectiveness of aggregation depends on two conditions: (a) the inability of the predator to consume all prey in a group and (b) detection of a single large group not being proportionally easier than that of several small groups. How prey aggregation influences predation rates when visual cues are restricted, such as in turbid water, has not been tho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…While taxa with high aggregation tendency predominated in the guts examined (>70%), the electivity index showed that B. meridionalis preferred those with weak aggregation tendency. Although aggregate assemblages make the group more conspicuous to predators, aggregation may be an antipredator adaptation to dilute the predation impact among neighbors (Wrona and Dixon 1991) and to respond faster to detecting danger (Johannesen et al 2014). Regarding prey feeding habits, shredders were the most vulnerable to predation, suggesting that fish preferred to forage on leaf litter substrates.…”
Section: Trait Prey Selectivitymentioning
confidence: 99%
“…While taxa with high aggregation tendency predominated in the guts examined (>70%), the electivity index showed that B. meridionalis preferred those with weak aggregation tendency. Although aggregate assemblages make the group more conspicuous to predators, aggregation may be an antipredator adaptation to dilute the predation impact among neighbors (Wrona and Dixon 1991) and to respond faster to detecting danger (Johannesen et al 2014). Regarding prey feeding habits, shredders were the most vulnerable to predation, suggesting that fish preferred to forage on leaf litter substrates.…”
Section: Trait Prey Selectivitymentioning
confidence: 99%
“…Studies of plasticity in responses of fish to changed environments tend to focus either on long-term rearing of juveniles (Chapman et al 2009(Chapman et al , 2010aEhlman et al 2015;Sakai et al 2016;Wright et al 2018) or short-term exposure of adults (Ward et al 2008;Johannesen et al 2012Johannesen et al , 2014Fischer and Frommen 2013;Kimbell and Morrell 2015a, b). Costly behaviourally plastic responses, such as increased activity (juvenile cod (G. morhua); Meager and Batty 2007) may be effective in the short term, but not sustainable over longer times cales, while mechanisms such as learning (Odling-Smee and Braithwaite 2003; Dukas 2013), physiological or morphological changes (Webster et al 2011) may allow responses to be maintained or improved.…”
Section: Introductionmentioning
confidence: 99%
“…A recent proposal is that the evolution of this aggregative behaviour in isopods occurred before any transition to land and may have brought ecological significance for animals other than reducing desiccation, such as protection from predators and helping individuals to find a suitable resting place (Broly et al, 2013). Some animals, including crustaceans and insects, use aggregative behaviour as a strategy for protection from predators (Johannesen et al, 2014;Svádová et al, 2014).…”
Section: Introductionmentioning
confidence: 99%